Changes in Resting-State Functional Connectivity of the Hippocampus Following Cognitive Effort Predict Memory Decline at Older Age—A Longitudinal fMRI Study - Oren, Noga; Ash, Elissa L.; Shapira-Lichter, Irit; Elkana, Odelia; Reichman-Eisikovits, Osnat; Chomsky, Lior; Lerner, Yulia (Frontiers in Aging Neuroscience, 2019)
Memory decline is a feature of some, but not all, healthy older adults. The neural patterns of this variability are still largely unknown. We examined the resting-state functional connectivity (RSFC) of older and younger adults before and after cognitive effort as an underlying feature for subsequent memory changes, focusing on the RSFC between the left anterior hippocampus (laHC) and the posterior hippocampi (pHC). Results showed that for younger adults, post-effort increases in laHC–pHC RSFC were related to increases in RSFC between the laHC and the hubs of the default mode network (DMN). However, for older adults, post-effort increases in the RSFC of laHC–pHC were related to decreases in the RSFC of the laHC and right precentral gyrus. Thus, the correlation between intra-HC and inter-HC RSFC was altered with cognitive effort and aging. Importantly, older adults who had lower post-effort RSFC between the laHC and the pHC demonstrated a decline in episodic memory 2 years later. Hence, the change in intra-HC RSFC following cognitive effort was able to predict subsequent memory function with aging in our sample.